2003
DOI: 10.1111/j.1346-8138.2003.tb00359.x
|View full text |Cite
|
Sign up to set email alerts
|

Non‐Melanoma Skin Cancers between the Years of 1990 and 1999 in Izmir, Turkey: Demographic and Clinicopathological Characteristics

Abstract: The incidence of nonmelanoma skin cancers (NMSCs) has been rapidly increasing in epidemic proportions all over the world. The purpose was to evaluate the demographic and clinico-pathological patterns of skin cancers in Izmir, a region with high ultraviolet light exposure. The study was retrospective and hospital-based. The data related to all NMSC patients registered from January 1, 1990, to December 31, 1999, in the Dermatology Department of Ege University Medical School in Izmir, were collected and analyzed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
15
0
5

Year Published

2004
2004
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(27 citation statements)
references
References 26 publications
7
15
0
5
Order By: Relevance
“…Similar to other studies in our country, the average age was found to be 65 in our study (3,8,9). Our cases peaked at seventh decade.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Similar to other studies in our country, the average age was found to be 65 in our study (3,8,9). Our cases peaked at seventh decade.…”
Section: Discussionsupporting
confidence: 91%
“…In our study, BCC incidence among patients with NMSC was 70% (n=84), which was consistent with the incidence in white Caucasians. SCC is the second most common skin cancer among white Caucasians, and constitutes 15% to 25% of all skin cancers (3,8,9). In our study, SCC covered 30% of the cases (n=36).…”
Section: Discussionmentioning
confidence: 46%
“…The pathogenesis of SCC is multifactorial, but excess UV exposure and having less skin pigmentation are the main factors [6]. In a study performed in İzmir, Turkey, the prevalence of SCC was found to be 26.6% among skin cancers other than MM [7]. In a study by Darjani et al [14] the SCC prevalence was reported to be 3.8%.…”
Section: Discussionmentioning
confidence: 99%
“…In literature, there are a few studies on skin malignancies and their prevalence in Turkey, especially in the geriatric population [4,6,7].…”
Section: Introductionmentioning
confidence: 99%
“…Bizim çalışmamızda da hastaların lezyonlarının %95,3'ü baş-boyun bölgesinde tespit edildi. BHK ile ilgili ülkemizde yapılan çeşitli çalışmalarda da bizim sonuçlarımıza benzer tespitler olduğu gözlendi (3,5,11).…”
Section: Introductionunclassified